Abdul Halim Hasan and His Contributions in Quranic Exegesis in the Malay World - Abdul Qadir Umar Usman Al-Hamidy; Muhammad Mustaqim Mohd.Zarif (Human Resource Management Academic Research Society, 2024)
Non-Indexed Publication